1983
DOI: 10.1177/000992288302200801
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for Exchange Transfusion in Newborn Infants

Abstract: The need for exchange transfusion was analyzed retrospectively using several different methods (total bilirubin binding capacity, birth weight, plasma protein level, and two published charts). These predictive methods were applied to 175 jaundiced infants for whom all the data were available and to 19 infants who were actually exchanged. Most of the patients were sick, premature infants. This study demonstrates the lack of agreement among the predictive methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The published literature also suggests that the indications for exchange transfusion are unclear. One retrospective study showed no agreement between five methods used to predict the need for such a transfusion ( Robertson et al ., 1983 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The published literature also suggests that the indications for exchange transfusion are unclear. One retrospective study showed no agreement between five methods used to predict the need for such a transfusion ( Robertson et al ., 1983 ).…”
mentioning
confidence: 99%
“…The published literature also suggests that the indications for exchange transfusion are unclear. One retrospective study showed no agreement between five methods used to predict the need for such a transfusion (Robertson et al, 1983).Bearing these factors in mind, we undertook this audit to establish current practice at hospitals supplied by the North London Blood Centre (NLBC) and to discover any divergence from existing guidelines (BCSH Blood Transfusion Task Force, 1994). The NLBC aims to issue blood of high specification for neonatal exchange transfusions.…”
mentioning
confidence: 99%
“…To facilitate this review, I would like to correct the inaccurate reference by Lorenz, which is located in the Journal of Pediatrics, not Pediatrics. 1 d o not underestimate the positive effect of well planned, individualized stimulation programs that are implemented after assessment of each infant's readiness for such interaction. I am concerned about the effects of overstimulation that can occur in the special care nursery, particularly with very low birth weight infants.…”
mentioning
confidence: 99%